Case report: Sandwich therapy of CAR-T combined with ASCT: Sequential CAR-T cell therapy with ASCT after remission with CAR-T therapy caused long-term survival in a patient with relapsed/refractory Burkitt’s lymphoma with TP53 mutations - Zhang, Qi; Zhu, Xiaojian; Liu, Bo; Zhang, Yicheng; Xiao, Yi (Frontiers in Immunology, 2023)
Burkitt's lymphoma (BL) with TP53 mutation often has poor outcome after standard chemoimmunotherapy. Adoptive chimeric antigen receptor (CAR)-T cell therapy may be a new paradigm for treating refractory/relapsed (r/r) BL, but its therapeutic effects remain inconclusive. Here, we report a patient with r/r BL who failed to achieve complete remission(CR) and progressed rapidly after multiple protocol chemotherapy. The patient achieved CR with CAR-T cell therapy, and obtained long-term disease-free survival after CAR19 and CAR22 T-cell cocktail therapy treatment and autologous hematopoietic stem cell transplantation (ASCT). The clinical evolution and genetic features of this case may provide some guidance for CAR-T therapy in overcoming relapses associated with TP53 gene mutations.